Statistical Communications in Infectious Diseases (De Gruyter, 2009)
Statistical Communications in Infectious Diseases (SCID) publishes significant research on the application of statistical ideas to problems arising from studies of infectious diseases. SCID takes a broad perspective on the role of statistics in infectious disease research including application, policy, education and theory.